Macro benefits from Micronutrient Zinc in the Malwa Plateau - Dixit, A. K.; Tomar, D. S.; Kaushik, S. K.; Tiwari, Rekha (Indian Farming, 2016)
Zinc is an important macronutrient in wheat and other crops. It is estimated that 50 percent of agricultural soils meant for crop cultivation are zinc deficient. Zinc is vital for many biological functions in the human body too. Its deficiency leads to many kind of physiological malfunctioning. KVK Ujjain is actively involved in the dissemination of technology to the farming community to restore the fertility status of soils, specially its zinc deficiency.